Quantification of trace fenuron in waste water samples by matrix matching calibration strategy and gas chromatography-mass spectrometry after simultaneous derivatization and preconcentration - Oflu, Sude; Erarpat, Sezin; Zaman, Buse Tugba; Eroglu, Kumsal; Gunkara, Omer Tahir; Bakirdere, Sezgin; Turak, Fatma (SPRINGER, 2023)
This study presents a highly sensitive and accurate analytical strategy for the determination of fenuron in wastewater samples using gas chromatography-mass spectrometry (GC-MS). Simultaneous derivatization and spray-based fine droplet formation-liquid phase microextraction (SFDF-LPME) method was developed and performed to achieve low detection limits. The parameters of the derivatization and SFDF-LPME method were optimized by univariate approach to improve sensitivity and selectivity. Under the optimum SFDF-LPME-GC-MS conditions, the limit of detection (LOD) and limit of quantitation (LOQ) were found to be 0.15 and 0.49 mg/kg, respectively. In addition, the linear range was calculated as 0.51-24.50 mg/kg. Recovery studies were carried out on wastewater samples to determine the accuracy of the developed method and its applicability to real sample matrix. Matrix matching calibration strategy was applied to eliminate/reduce any possible interference effects caused by the complexity of the wastewater matrix and to increase the accuracy of the analytical results. Percent recovery results varied between 85.9 and 120.9% with small percent relative standard deviation values. These results were satisfactory in terms of the accuracy and applicability of the proposed method for wastewater samples.
Keywords: Fenuron; Derivatization; Gas chromatography-mass spectrometry; Wastewater; Spraying-based fine droplet formation-liquid phase microextraction; PHENYLUREA HERBICIDES; LIQUID-CHROMATOGRAPHY; SURFACE-WATER; PESTICIDES; UV; DIURON; RICE; Environmental Sciences & Ecology